Service Website Implementation Use Laboratory For Faculty Science and Technology of Universitas PGRI Yogyakarta - Japeiter, Hilton; Setia Wardani; Putri, Puji Handayani (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2024)
The purpose of study is develop service website use laboratories in the Faculty Science and Technology (FST) for increase efficiency , effectiveness and quality service laboratory . This website will help to unravel Variety problems found in the FST laboratory , such as lack of source Power human (HR), limitations capacity , availability and quality services , as well as lack of information about needs , demands , and feeds come back from user laboratory.Website This will provide Features like confirmation use laboratory , inventory and reporting use laboratory online . This website will also give Variety information latest as well as accurate regarding conditions , and facilities laboratory.Development of this website expected can increase efficiency , effectiveness and quality service laboratory for its users . This website can also help manager laboratory in carry out monitoring and maintenance equipment laboratory , so that can minimize damage equipment laboratory and extend age equipment laboratory.Website This will built with use modern web technologies such as HTML, CSS, JavaScript, and PHP. This website will also using MySQL database for store user , laboratory , and equipment data laboratory.research This expected Can give benefit especially in improvement quality service laboratory at FST.